Performance Evaluation of Centralized Reconfigurable Transmitting Power Scheme in Wireless Network-on-chip - M. S. Rusli; A. A. H. Ab Rahman; U. U. Sheikh; N. Shaikh Husin; Michael L. P. Tan; T. Andromeda; M. N. Marsono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Network-on-chip (NoC) is an on-chip communication network that allows parallel communication among all cores to improve inter-core performance. Wireless NoC (WiNoC) introduces long-range and high bandwidth radio frequency (RF) interconnects that can possibly reduce the multi-hop communication of the planar metal interconnects in conventional NoC platforms. In WiNoC, RF transceivers account for a significant power consumption, particularly its transmitter, out of its total communication energy. This paper evaluates the energy and latency performance of a closed loop power management mechanism which enables transmitting power reconfiguration in WiNoC based on number of erroneous received packets. The scheme achieves significant energy savings with limited performance degradation and insignificant impact on throughput.